Drawings since 1960. : A Selection of the Collection of Drawings of the Stedelijk Museum. - Beeren, W.A.L.; Petersen, Ad; Poot, Jurrie (Amsterdam : Stedelijk Museum Amsterdam, 1989)
van Altena, Allie ; Anselmo, Giovanni ; Blais, Jean-Charles ; Blom, Ansuya ; van den Broeck, Frank ; Couzijn, Wessel ; Cucchi, Enzo ; Cutrone, Ronnie ; Dahn, Walter ; Disler, Martin ; van den Dobbelsteen, Jan ; Dumas, Marlene ; Evans, Donald ; Fontana, Lucio ; Galan, Julio ; Gudmundsson, Sigurdur ; Henneman, Jeroen ; Heyboer, Anton ; Hollein, Hans ; Kienholz, Edward ; van Koningsbruggen, Rob ; Kounellis, Jannis ; Kupferman, Moshe ; LeWitt, Sol ; Lucebert ; Mangold, Robert ; De Maria, Nicola ; Morellet, François ; Nauman, Bruce ; Oldenburg, Claes ; Polke, Sigmar ; Raetz, Markus ; Ruscha, Edward ; Salvo ; Schoonhoven, Jan ; Shapiro, Joel ; Slits, Ton ; Thomkins, André ; Topor, Roland ; Tremlett, David ; Tuttle, Richard ; Verkerk, Emo ; Visser, Carel ; Westerik, Co
Engels
boek